ANALISA TINGKAT PENDAPATAN IMBAL JASA PENJAMINAN (IJP) DARI PENJAMINAN ATAS KREDIT DAN PENGUKURAN KINERJA PERUSAHAAN PADA PT. JAMKRIDA BABEL - Fitriansyah, Andry; Novika; Panjaitan, Fery (Jurnal Akuntansi Bisnis Dan Keuangan, 2023)
This study intends to dissect the level of Guaranteed Fee (IJP) which was obtained for the main business of the credit guaranteed company and the Organizational Performance at PT. Jamkrida Babel. The research uses a quantitative investigative strategy approach and aims to investigate the income based on Guaranteed Fee (IJP) and its impact toward The Organizational Performance based on the financial perspective of fiscal year 2019 - 2020 at PT. Jamkrida Babel. The results of this study indicate that there has been a significant decrease experienced by PT. Jamkrida Babel in fiscal year 2020 compared to 2019. The finding was clear on The Productive or non-Productive revenue based on Guaranteed Fee (IJP) was decreased by 8.93%. Therefore, the finding was linier toward the company performance in fiscal year 2020 which is stated on a financial perspective instrument; ROE (-3.79%), ROA (-3.20%) and Net Profit (-219,29%). This research concludes that it is important for companies to reach a financing relationship with banking institutions by trying to approach the business entities-community and establishing market segmentation for small and medium enterprises in the regions. With this result, it is expected that the income from the Fee Guaranteed for both Productivity and Non-Production will increase and it would be affected positively toward Net Profit, Return on Equity and Return on Assets of the firm.